Feline cardiac lymphoma: a case report - Magalhães, Henrique Inhauser Riceti; Mendonça, Karen Gonçalves; de Paula, Ygor Henrique; Romão, Fabiano Braz; Barcelos, Jeferson Borges; Dobritz, Wanessa Ribeiro Gontijo; Pichioni, Vera Lucia; dos Santos, Thaisa Reis (Brazilian Journal of Veterinary Medicine, 2019)
Cancer is the main cause of death among pet animals. FeLV, the feline leukemia virus, increases the odds of domestic felines’ developing lymphoma or leukemia 62 fold. The cardiac lymphoma is a rare neoplasia and little is known about it in Veterinary Medicine. Therefore, it has been sought to report a case of cardiac lymphoma in a two-year-old, FeLV-positive feline patient, who presented dyspnea, lack of appetite, progressive loss of weight, and apathy. By means of supplementary examination, the presence of a mass attached to the heat would be verified, and lymphoma was diagnosed upon histopathological examination. It is thus concluded that this neoplasia was associated to the feline leukemia virus and that, in spite of the supplementary examinations’ having been utterly important for a correct diagnosis, the lack of an early definition aggravated the clinical picture of the patient and hindered the implementation of specific treatment.